Cervical Cystic Lymphangioma in Child: A Case Report - Nurzawani S; Mohd Aznan MA (Asian Journal of Medicine & Health Sciences, 2024)
Lymphangiomas are benign swellings of the neck which can occur among the paediatric population. They are fluid-filled sacs that result from obstruction in the lymphatic system. Most of the cases are diagnosed at birth and 95% of them are found in the neck, head, or axilla. Lymphangiomas typically present surgical obstacles and difficulties due to their propensity to invade and disseminate across nearby structures. We report the case of a 3-year-old child who presented with progressive lateral cystic cervical neck swelling for 4 months. Surgical excision of the lesion was performed. The final histopathological diagnosis was lymphangioma. A 6 month follow up shows no recurrence and a cosmetically acceptable scar.